Local Currency Debt Markets in the West African Economic and Monetary Union - Sy, Amadou (IMF Working Papers; Working Paper ;, 2007)
The paper reviews trends and developments in the rapidly growing local currency debt markets in the WAEMU. The main findings are that common institutions, such as a regional central bank and securities exchange have led to high cross-border transactions within the union. However, excess liquidity in the regional banking system has led to limited credit differentiation among issuers and a reliance on supply and demand conditions as a key determinant of yields. The paper also discusses a number of policy issues, including debt management, that are likely to emerge as the markets for government securities continue to develop.